\(3^{x+1}\)+ \(3^x\) = 108

 

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(3^{x+1}+3^x=108\)

\(\Rightarrow3^x\left(1+3\right)=108\)

\(\Rightarrow3^x.4=108\)

\(\Rightarrow3^x=108:4\)

\(\Rightarrow3^x=27\)

\(27=3^3\)

\(3^x=3^3\)

\(\Rightarrow x=3\)

Vậy x = 3

11 tháng 12 2019

3\(^{x+1}\)+ 3\(^x\)=108

3\(^x\).3 + 3\(^x\)= 108

3\(^x\)( 3 + 1 ) = 108

3\(^x\). 4 = 108

3\(^x\)= 27 = 3\(^3\)

x = 3

9 tháng 4 2018

4,

a,\(\dfrac{x-1}{9}\)=\(\dfrac{8}{3}\)

[x- 1].3=9.8

[x- 1].3=72

x-1=72:3

x-1=24

x=24+1

x=25

2 tháng 5 2020

kết quả thì mình ko chắc

31 tháng 8 2018

\(3^{x+1}+3^x=108\)

\(3^x\cdot3+3^x=108\)

\(3^x\cdot\left(3+1\right)=108\)

\(3^x=27=3^3\)

\(\Rightarrow x=3\)

31 tháng 8 2018

\(3^{x+1}+3^x=108\)

(=)\(3^x.3+3^x=108\)

(=)\(3^x.\left(3+1\right)=108\)

(=)\(3^x.4=108\)

(=)\(3^x=27\)

(=)\(3^x=3^3\)

=>x=3

20 tháng 6 2018

e) \(\frac{-84}{14}< 3x< \frac{108}{9}\)

\(\Rightarrow-2< x< 4\)

Vậy \(-2< x< 4\)

d)  \(\frac{x-3}{y-3}=\frac{4}{3}\)

Ta có: x=y+5

\(\Rightarrow\frac{y+5-3}{y-3}=\frac{4}{3}\)

\(\Rightarrow\frac{y+2}{y-3}=\frac{4}{3}\)

\(\Rightarrow\left(y+2\right).3=\left(y-3\right).4\)

\(3y+6=4y-12\)

\(6+12=4y-3y\)

\(y=18\)

\(\Rightarrow x=5+y=5+18=23\)

KL:............................

20 tháng 6 2018

a) \(\frac{x-1}{9}=\frac{8}{3}\)

\(\Rightarrow\)\(\left(x-1\right).3=9.8\)

\(3x-3=72\)

\(3x=75\)

\(x=\frac{75}{3}\)

\(x=25\)

Câu b tương tự

\(\frac{x}{4}=\frac{18}{x+1}\)

\(\Rightarrow x.\left(x+1\right)=4.18\)

\(x.\left(x+1\right)=72\)

\(x.\left(x+1\right)=8.9\)

\(\Rightarrow x=8\)

14 tháng 9 2016

\(3^{x+1}+3^x=108\)

\(\Leftrightarrow3^x\left(3+1\right)=108\)

\(\Leftrightarrow3^x=27=3^3\)

\(\Leftrightarrow x=3\)

5 tháng 12 2020

\(A\frac{27^4.8^{17}}{9^6.32^3}=\frac{\left(3^3\right)^4.\left(2^3\right)^{17}}{\left(3^2\right)^6.\left(2^5\right)^3}=\frac{3^{12}.2^{51}}{3^{12}.2^{15}}=\frac{3^{12}.2^{15}.2^{36}}{3^{12}.2^{15}}=2^{36}\) 

\(B=\frac{72^3.54^3:8^3}{108^5:4^5}=\frac{\left(72.54:8\right)^3}{\left(108:4\right)^5}=\frac{486^3}{27^5}=\frac{\left(3^5.2\right)^3}{\left(3^3\right)^5}=\frac{3^{15}.2^3}{3^{15}}=2^3=8\) 

Bài 2 

A = 2 +22 + 23 + 24 + ....+ 2100 

A = ( 2+22 ) + (23 + 24 ) + ....+ (299 + 2100 )

A = 2(1+2 ) + 23 (1+2 ) + ...+ 299(1+2) 

A = 2.3 + 23.3 + ....+ 299 .3 

A = 3(2+23 + ...+ 299 )  

=> A \(⋮\) 3 ( đpcm ) 

Bài 3 

a, 2.3x = 312 .34 + 20 .274 

2.3x = 312  . 34 + 20 . (33 ) 4 

2.3x = 312 .34 + 20 .312

2.3x = 312(34+20 ) 

2.3x = 312 . 54 

2.3x = 312 . 27 .2 

2.3x = 312 . 33 .2 

2.3x = 315 .2 

=> x=15 

b , (2x +1 ) 2 + 3.(22 + 1 ) = 22 .10 

 (2x +1 ) 2  + 3.(4+1 ) = 4.10 

 (2x +1 ) 2  + 3.5 = 40 

(2x +1 )  + 15 = 40 

(2x +1 )  = 40-15

(2x +1 )  = 25 

(2x +1 )   = 52 

=> 2x + 1 = 5 

2x  = 5-1 

2x = 4 

2x = 22 

=> x=2 

6 tháng 8 2016

1)

\(\frac{7.8^3-5.2^{10}}{\left(-16\right)^2}\)       

=  \(\frac{7.2^8.2-5.2^8.2^2}{16^2}\)

=  \(\frac{2^8.\left(2.7-5.2^2\right)}{2^8}\)

=   \(\frac{2^8.\left(-6\right)}{2^8}\)

=   \(-6\)

 

6 tháng 8 2016

2)

b)\(\frac{-28}{4}\le x\le\frac{-21}{7}\)

\(\Rightarrow-7\le x\le-3\)

\(\Rightarrow x=\left\{-7;-6;-5;-4;-3\right\}\)

Tìm x :

a) \(2.x.\frac{-3}{4}=-\frac{5}{12}\)

\(\Rightarrow2x=-\frac{5}{12}:-\frac{3}{4}\)

\(\Rightarrow2x=\frac{5}{9}\)

\(\Rightarrow x=\frac{5}{9}:2\)

\(\Rightarrow x=\frac{5}{18}\)

Vậy : \(x=\frac{5}{18}\)

b) \(\frac{2}{3}+\frac{1}{3}.x=7\)

\(\Rightarrow\frac{1}{3}.x=7-\frac{2}{3}\)

\(\Rightarrow\frac{1}{3}.x=\frac{19}{3}\)

\(\Rightarrow x=\frac{19}{3}:\frac{1}{3}\)

\(\Rightarrow x=19\)

Vậy : \(x=19\)

c) \(\left(4.x+\frac{1}{8}\right)=\frac{3}{10}\)

\(\Rightarrow4.x=\frac{3}{10}-\frac{1}{8}\)

\(\Rightarrow4.x=\frac{7}{40}\)

\(\Rightarrow x=\frac{7}{40}:4\)

\(\Rightarrow x=\frac{7}{160}\)

Vậy : \(x=\frac{7}{160}\)

d) \(\frac{1}{3}.x-5=1\frac{1}{2}\)

\(\Rightarrow\frac{1}{3}.x-5=\frac{3}{2}\)

\(\Rightarrow\frac{1}{3}.x=\frac{3}{2}+5\)

\(\Rightarrow\frac{1}{3}.x=\frac{13}{2}\)

\(\Rightarrow x=\frac{13}{2}:\frac{1}{3}\)

\(\Rightarrow x=\frac{39}{2}\)

Vậy : \(x=\frac{39}{2}\)

e) \(-\frac{2}{3}.x+\frac{1}{3}=-\frac{1}{2}\)

\(\Rightarrow-\frac{2}{3}.x=-\frac{1}{2}-\frac{1}{3}\)

\(\Rightarrow-\frac{2}{3}.x=-\frac{5}{6}\)

\(\Rightarrow x=-\frac{5}{6}:\left(-\frac{2}{3}\right)\)

\(\Rightarrow x=\frac{5}{4}\)

Vậy : \(x=\frac{5}{4}\)